2015
DOI: 10.4102/phcfm.v7i1.755
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use amongst learners in rural high school in South Africa

Abstract: BackgroundDrinking behaviour by adolescents is a significant public health challenge nationally and internationally. Alcohol use has serious challenges that continue to deprive adolescents of their normal child growth and development. Drinking is associated with dangers that include fighting, crime, unintentional accidents, unprotected sex, violence and others.AimThe aim of the study is to investigate drinking patterns, and factors contributing to drinking, amongst secondary school learners in South Africa.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
36
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 13 publications
6
36
2
Order By: Relevance
“…Indeed, students with friends who consumed alcohol were seven times more likely to consume alcohol than those without. This finding concurs with the results of other studies [42,43]. For example, a study that was conducted in Thailand showed that peer influence has a significant impact on the initiation to alcohol consumption among youth [17].…”
Section: Characteristicssupporting
confidence: 92%
“…Indeed, students with friends who consumed alcohol were seven times more likely to consume alcohol than those without. This finding concurs with the results of other studies [42,43]. For example, a study that was conducted in Thailand showed that peer influence has a significant impact on the initiation to alcohol consumption among youth [17].…”
Section: Characteristicssupporting
confidence: 92%
“…Of the current drinkers in this study, 62% were males and 38% were female. These results resonate with studies by (Flisher, Parry, Evans, Muller, & Lombard, 2003;Leteka, 2007;Chauke, van der Heever, & Hoque, 2015) which showed that males are more prone to drinking alcohol than females.…”
Section: Discussionsupporting
confidence: 91%
“…There was an even split between ciders in the survey, with the majority of both male and female respondents indicating that their drink of choice was cider. Earlier research by Newman, Shell, Ming, Jianping, and Maas, (2006) and later research by Chauke et al, (2015), both show that wine is a drink of choice for women whereas men prefer to drink beer. The current study has however also revealed that there is a small percentage (5.6%) of young people who drink traditional beer and some who drink all sorts of alcohol they can have access to.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This group of adolescents tend to be more socioeconomically disadvantaged and live in households where the average per capita household income is low (27). Another study conducted in a rural school in Gauteng province found that both males and females drank high amounts of alcohol in the past month (127). Yet, this study did not take into consideration the association between financial difficulties and alcohol use.…”
Section: Discussionmentioning
confidence: 81%